Warm weather leads to safe choices - MADAN, Shilpa (Institutional Knowledge at Singapore Management University, 2017)
Consumers have different purchase journeys depending on the temperature, according to research; and not just when it comes to purchasing cold drinks.Writing for WARC, Shilpa Madan, an Associate at the Institute on Asian Consumer Insight (ACI) in Singapore, explains that outward bodily sensations, such as feeling hot in summertime, can influence the way consumers perceive people and things, and shape preferences and choices, without conscious thought.